การเตรียมเซริซินและไฟโบรอินจากรังไหมบ้านและรังไหมป่า - พุธิตา คงจังหวัด (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Silk is a natural fibers. There are two important proteins, Fibroin (body of silk fiber) is 70-80% and sericin (silk glue) is 20-3-%. The special properties of two proteins can be used as drugs and cosmetics etc. This research was studied the degumming of native and wild silkworm cocoons. The analysis with 2 factorial was applied to determine the effect of parameters, which were ratio of silkworm cocoons to water, temperature and time and the second part of 2 factorial were ratio of silkworm cocoons to Na₂Co₃ solution, concentration of Na₂Co₃ temperature and time and study the degumming of native and wild silkworm cocoons with water under pressure. The results showed that the silkworm cocoons were degummed 9.26% and 6.31% respectively with water at 100 C and 120 minutes with twice repeated treatment. The remained fiber were degummed with 0.5% Na₂Co₃ at 100 ℃, 90 minutes for native silkworm cocoons and 120 minutes for wild silkworm cocoons. The sericin extract are 8.54% and 5.98% while the pure fibroin are 763.85% and 80.05% respectively. In case of degumming of native and wild silkworm cocoons with water under pressure at 150 ℃ and 120 minutes. The native and wild silkworm cocoons were degummed 24.75% and 18.26% respectively. The sericin extract are 20.12% and 13.94% while the final obtained pure fibroin are 74.96% and 80.12% respectively.